Unveiling Curators’ Accountability in Inaccessible Bankruptcy Estates: Legal Hurdles and Debtor Defiance - Wahyu Aji Susanto; Valerio Sebastian; Siti Aminatun Nasifah Ahmad Malik (Universitas Negeri Semarang, 2025)
This article analyzes the critical role of curators in managing bankruptcy estates, with a particular focus on the challenges they face when debtors obstruct access to assets, hindering the insolvency process. Under Indonesia’s Law No. 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations, curators are authorized to access and manage the bankruptcy estate without debtor consent. However, in practice, curators often encounter resistance, such as being denied entry to business premises or access to essential documents. This obstruction not only complicates the curator's duties to inventory, secure, and liquidate assets but also poses significant risks to creditors' interests. Through a doctrinal research approach, this study examines the legal responsibilities and potential remedies available to curators when faced with debtor non-cooperation. The research highlights that while curators have substantial legal duties, their accountability should be assessed in proportion to the efforts made to overcome debtor resistance, such as reporting to the supervisory judge, seeking forced execution, and taking anticipatory actions against asset concealment. Furthermore, curators have access to several legal remedies, including coordination with supervisory judges, law enforcement intervention, and filing a lawsuit for asset cancellation (actio pauliana) in cases of fraudulent asset transfers. The article contributes to the discourse on insolvency law by proposing legal reforms to enhance curator authority and protect creditors’ rights. It argues for more robust enforcement mechanisms to ensure the efficiency and fairness of the bankruptcy process, offering valuable insights for legislators, legal practitioners, and scholars seeking to address the complexities of debtor non-cooperation.